2018
DOI: 10.1001/jamapsychiatry.2017.4040
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Transcranial Direct Current Stimulation as an Add-on Treatment for Bipolar Depression

Abstract: clinicaltrials.gov Identifier: NCT02152878.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 47 publications
8
58
1
5
Order By: Relevance
“…The interventions were 12 tDCS sessions or sham (10 sessions once a day for 2 weeks and then one session every other week until week 6). The main outcome was that active tDCS was superior to sham (Sampaio‐Junior et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interventions were 12 tDCS sessions or sham (10 sessions once a day for 2 weeks and then one session every other week until week 6). The main outcome was that active tDCS was superior to sham (Sampaio‐Junior et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited and enrolled as described in previously published studies ELECT‐TDCS (Brunoni et al., ) and BETTER (Sampaio‐Junior et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Recently, a meta-analysis suggested that tDCS could also be a potential and well-tolerated therapeutic option for patients with bipolar disorder (BD) experiencing a major depressive episode (MDE) for which standard treatments are often inefficient and/or associated with a risk of manic switch. 2,3 We report here the case of a patient with a history of bipolar depression, with a severe intolerance to medications in the context of a comorbid spinocerebellar ataxia (SCA), who achieved full symptomatic recovery after being treated with tDCS over a 2-week protocol (Figure 1). Mrs R is a 70-year-old patient who fulfilled the DSM-5 diagnostic criteria for type I BD and consulted our Psychiatry Department for a treatment-resistant MDE (Montgomery-Asberg Depression Rating Scale (MADRS) = 38/60).…”
mentioning
confidence: 99%